Proceeding: International Conference of Medical and Health Sciences 2015 - leveraging multidiciplinary collaboration to improve healthcare quality and equity - Titih Huriah, Tetsuo Ichikawa (UMY Press, 2015)
Proceeding: International Conference of Medical and Health Sciences 2015 - leveraging multidiciplinary collaboration to improve healthcare quality and equity